Trajetórias de formadores/as de educadores/as de pessoas jovens e adultas no Brasil - da terra para o papel: elementos necessários para a formação do/a educador/a - Clarice Wilken de Pinho (2022)
Through this work, we seek to know the trajectories of trainers of youth and adult educators in Brazil. As a central question we tried to answer who, when and where these people have worked in the training of Youth and Adult Education (YAE) educators, throughout their trajectories. Our reflections delved into discussions about the elements necessary for the training of this educator, in dialogue with Arroyo (2017); Brandão (2002); Fávero (2006); Freire (2014); Jara (2020); Soares (2003); Vieira (2006), among others. As a methodological path, we conducted a survey of names of reference in the history of YAE and selected five educators with long and diverse trajectories: Maria Amélia Gomes de Castro Giovanetti (MG), Timothy Denis Ireland (PB), Elza Maria Fonseca Falkembach (RS), Edna Castro de Oliveira (ES) and Sérgio Haddad (SP). As a criterion for our choice, we sought to contemplate men and women from different regions of the country, who worked both in universities and in other formative spaces. We chose to understand their trajectories through autobiographical accounts, since this methodology allows us to rescue the significant memories of these people (PASSEGGI; SOUZA, 2017; DELORY-MOMBERGER, 2005). We can affirm that the educators of young and adult people contribute to the training of other people according to the experiences they have accumulated, with Popular Education has an important role in their life-long reflections-actions-reflections. About its relevance, we consider that the present work contributes to the debate about the body of knowledge necessary to train professionals to work in this area, therefore, to the search for quality in YAE.